Aleksej Vasil’‎evich Pogorelov is a mathematician of surprising forсe - Borisenko, A. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
It is described principal mathematical results, obtained by great mathematician A. V. Pogorelov and his life. Mathematics Subject Classification: 53C45, 35J60.